STUDI KRITIS KONSEP KESEHATAN REPRODUKSI WANITA DALAM CONVENTION ON THE ELIMINATION OF ALL FORMS DISCRIMINATION AGAINST WOMEN (CEDAW) MENURUT TINJAUAN ISLAM - Wulandari, Dewi (Muhammadiyah University Press, 2015)
As one of the international covenant that had been ratified by Indonesia through UU No. 7 Tahun 1984, CEDAW had been made several consequences like abortion legalization and easy access of contraception. One thing must be noticed that CEDAW didnât mention marriage as a must, as we can review from ICPDâs definition about reproductive health in women. ICPD was a dynamic response from CEDAW. As a convention emerged from Westâs worldview, Indonesia as an adoption country, must doing strict selection because CEDAW can be mean of infiltration Westâs worldview. The formulation of this research are how the concept on reproductive health women in CEDAW and how Islamâs critics toward the concept of reproductive health women in CEDAW. The aim of this research is to know the concept of reproductive health in women and how Islam critics about that concept. The method of this research was library research, with specifically analysis documents. The researcher using content analysis to analysis the content of the documents. Overall, researcher use deductive method for analysis. The findings from concluding commentsâ documents, CEDAWâs committee feedback about application CEDAW in Indonesia, is feminism value. The point is women have fully freedom to decide all the problems in her reproductive health without intervention by her husband, her family, country or religion. Islam has point of critics start from difference on worldview. Islam as worldview has its paradigm towards several concepts, like concept of God, concept of divine, concept of prophet, etc.